2016
DOI: 10.1080/15459624.2016.1179388
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the framework for considering the effects of climate change on worker safety and health

Abstract: In 2009, a preliminary framework for how climate change could affect worker safety and health was described. That framework was based on a literature search from 1988–2008 that supported seven categories of climate-related occupational hazards: (1) increased ambient temperature; (2) air pollution; (3) ultraviolet exposure; (4) extreme weather; (5) vector-borne diseases and expanded habitats; (6) industrial transitions and emerging industries; and (7) changes in the built environment. This paper reviews the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 136 publications
1
113
0
1
Order By: Relevance
“…The interest in the impact of heat‐related events on workers’ health and safety has recently increased. Studies have demonstrated that intense and prolonged occupational exposure to elevated temperatures has been associated with health effects, such as dehydration and spasms, increased fatigue, and reduced productivity . The increased risk of workplace injuries may be the consequence of sweaty palms, fogged‐up safety glasses, dizziness, and reduced cognitive performance .…”
Section: Discussionmentioning
confidence: 99%
“…The interest in the impact of heat‐related events on workers’ health and safety has recently increased. Studies have demonstrated that intense and prolonged occupational exposure to elevated temperatures has been associated with health effects, such as dehydration and spasms, increased fatigue, and reduced productivity . The increased risk of workplace injuries may be the consequence of sweaty palms, fogged‐up safety glasses, dizziness, and reduced cognitive performance .…”
Section: Discussionmentioning
confidence: 99%
“…This number is most likely underestimated given that criteria to determine heat‐related deaths vary by state (CDC, ) and heat exposure may not be recorded as the primary cause of death (Berko, Ingram, Saha, & Parker, , July 30; Leigh, Du, & McCurdy, ; Oberlin, Tubery, Cances‐Lauwers, Ecoiffier, & Lauque, ; Ostro, Roth, Green, & Basu, ). Increasing ambient temperatures resulting from climate change are a recognized climate‐related occupational hazard (Schulte et al., ) and have profound effects on human health (Perera, ). Average surface temperatures have been rising since 1901, with the past decade (2006–2015) being the warmest ever recorded (Environmental Protection Agency, ).…”
mentioning
confidence: 99%
“…Average surface temperatures have been rising since 1901, with the past decade (2006–2015) being the warmest ever recorded (Environmental Protection Agency, ). Populations most adversely impacted by HRI include the elderly, children, low‐income, and outdoor workers, including farmworkers (Balbus & Malina, ; Schulte et al., ). Farmworkers’ risk for heat‐related death is nearly 20 times greater than that of other outdoor workers (Centers for Disease & Prevention, ).…”
mentioning
confidence: 99%
“…Aedes mosquitoes are primarily daytime biters and prefer to take blood meals after sunrise and in late afternoon, although at least one study has shown that they will bite in the evening under artificial lights (Chadee & Martinez, 2000). Groups more likely to be exposed to Aedes bites include children (more likely to play outside) and outdoor workers (Bennett & McMichael, 2010, Schulte et al, 2016. Those who tend to have homes that are more permeable (e.g., open windows instead of air conditioning and broken window screens) are also more likely to receive mosquito bites (Radke et al, 2012, Reiter et al, 2003.…”
Section: Selection and Projection Of Vulnerable Population Groupsmentioning
confidence: 99%